Level Set and PDE Based Reconstruction Methods in Imaging Cetraro, Italy 2008, Editors: Martin Burger, Stanley Osher - Burger, Martin; Mennucci, Andrea C.G; Osher, Stanley; Rumpf, Martin (C.I.M.E. Foundation Subseries, 2013)
This book takes readers on a tour through modern methods in image analysis and reconstruction based on level set and PDE techniques, the major focus being on morphological and geometric structures in images. The aspects covered include edge-sharpening image reconstruction and denoising, segmentation and shape analysis in images, and image matching. For each, the lecture notes provide insights into the basic analysis of modern variational and PDE-based techniques, as well as computational aspects and applications.